Mitigating the Impact of the Economic Crisis on Public Sector Health Spending - Schneider, Pia (World Bank, Washington, DC, 2012)
The current global financial crisis is having a substantial impact in Europe and Central Asia (ECA) where economic growth is beginning to dip, unemployment is rising and government revenues are being cut. The Gross Domestic Product (GDP) growth rate of the region is projected to decline by 4.7 percent in 2009 and the flow of remittances is also expected to slow down sharply, causing particular hardship to low-income groups. While countries with fiscal capacity have adopted stimulus packages to promote economic recovery, most ECA countries are financially constrained and have revised their government budgets, including in the health sector. Thus, as a result of the crisis, public spending on health may actually decrease in absolute amounts and in percentage of GDP. The health sectors in most ECA countries are mainly financed from public sources. In countries with low levels of public spending on health3, the majority of health services are paid for by patients. Any reductions in public health spending would thus only add to the out-of-pocket expenditures of patients, and may negatively affect access to care, particularly for the poor. There is increasing empirical evidence that public sector spending improves health indicators in low-income and transition countries, particularly in countries that have good governance systems in place.